Yield Assessment of Tree Resources Outside the Forest Using Sector Sampling: A Case Study of a Public Park, Bangkok Metropolis, Thailand - Phatcharapan Tongson,; Khwanchai Duangsathaporn,; Patsi Prasomsin, (Agriculture and Natural Resources, 2011)
The objectives of this study were to determine a suitable sector angle for a sector sampling inventory of trees outside the forest (TROF), and yield assessment of volume, diversity, biomass, and carbon storage at Wachirabenchatat Park, Bangkok metropolis, Thailand. Three angle sizes of 5, 10, and 15 ° were examined. In each angle size, eight sectors were randomly selected within the same study area, emanating from the same pivot point but going in different directions. The results showed that an angle size of 5 ° was suitable for sector sampling because of the slightly lower relative standard errors (SE%) of the tree volume and similar diversity index estimates, when compared with the other sector angles. From a study of the coefficient of variation of tree volume, the suitable number of sample sectors was six (sample size), for sampling in a similar study area. The results of a yield assessment study in Wachirabenchatat Park using an angle of 5 ° included estimates of biodiversity, volume, biomass and carbon storage estimates of trees. Twenty nine unique species were identified, the total volume of tree stems was 910.72 m3 (15.0 m3/ha); the total tree biomass and carbon storage in this selected area were 559.58 and 279.79 tonnes, respectively.